PENANGANAN LIMBAH B3 MASKER MELALUI UPAYA PEMBERDAYAAN UNTUK MENCEGAH PENULARAN COVID 19 DI KELURAHAN PEMATANG SULUR KOTA JAMBI (SMP IT NURUL ILMI) - Lesmana, Oka; Guspianto, Guspianto; Kusmawan, David (Jurnal Salam Sehat Masyarakat (JSSM), 2024)
The management of B3 waste and masks in the household is a problem that often arises in the community, especially during the COVID-19 pandemic, so that it has the potential to have a negative impact on human health and the environment. The results of this community service activity include: (1) Increased knowledge about the management of B3 waste and household waste (masks) in an effort to prevent COVID-19 through outreach activities based on Circular No. SE.3/MENLHK/PSLB3/PLB .3 /3/2021 Concerning the Management of B3 Waste and Waste from Handling Corona Virus Disease 19, (2) Improvement of skills related to the management of B3 waste and mask waste in households through community empowerment in managing B3 waste and masks in their respective homes, and (3) The formation of an Anti-COVID-19 group in the community. Based on the results of this activity, it can be concluded that the knowledge and skills of the community regarding the management of B3 waste and waste (masks) in the household can be improved through socialization, partnerships, and community empowerment.